Clays and Clay Minerals, Vol. 60, No. 4, 341–347, 2012. - Liu, Xiandong; Meijer, Evert Jan; Lu, Xiancai; Wang, Rucheng (The Clay Minerals Society, 2012)
Using first-principles molecular-dynamics simulations, probable inner-sphere complexes of Fe2+ adsorbed on the edge surfaces of clay minerals were investigated. Ferrous ions are important reductants in natural processes and their properties can be altered significantly by complexation on edge surfaces of clay minerals. However, the microscopic picture of adsorption sites and structures of Fe2+ is difficult to reveal with modern experimental techniques and, therefore, remains unclear. From the results of first-principles molecular-dynamics simulations, evidence has been provided that complexes on:Si-O sites were the most stable forms, which should be responsible for the experimentally observed pHdependent uptake. Such complexation was found to be strong enough to distort the local coordination structures of Si-O tetrahedra in the substrate. Analyses showed that Fe2+-Owater coordination structures were dominated by the solvent with surface groups participating in the complexes via H bonding. The present study provided a microscopic basis for understanding the chemical processes involving surfacecomplexed Fe2+ ions.
First-principles Molecular Dynamics Insight Into Fe2+ Complexes Adsorbed On Edge Surfaces Of Clay Minerals
gsccm60401-liu.pdf -- 1,641KB
Keywords: Periodicals; Geology; Complexation; Edge Surface; Ferrous Ion; First-principles Molecular Dynamics; Hydration